2016
DOI: 10.1039/c6en00146g
|View full text |Cite
|
Sign up to set email alerts
|

The use of metallic oxide nanoparticles to enhance growth of tomatoes and eggplants in disease infested soil or soilless medium

Abstract: Foliar application of CuO nanoparticles applied to tomato and eggplant grown in pathogen infested soil had more yield than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
193
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(205 citation statements)
references
References 29 publications
7
193
5
Order By: Relevance
“…Copper oxide nanoparticles (CuONPs) are globally produced (Keller et al 2013) for industrial applications in sensors, catalysts, solar energy conversion, electronic printing, surfactants, and antimicrobials (Bondarenko et al 2012;Wang et al 2013;Ahamed et al 2013). They also have potential use in agriculture, as a nutrient source or as a pesticide (Monreal et al 2015;Elmer and White 2016;Dimkpa and Bindraban 2017;Rodrigues et al 2017). Application of these products in agriculture may contribute to their environmental accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Copper oxide nanoparticles (CuONPs) are globally produced (Keller et al 2013) for industrial applications in sensors, catalysts, solar energy conversion, electronic printing, surfactants, and antimicrobials (Bondarenko et al 2012;Wang et al 2013;Ahamed et al 2013). They also have potential use in agriculture, as a nutrient source or as a pesticide (Monreal et al 2015;Elmer and White 2016;Dimkpa and Bindraban 2017;Rodrigues et al 2017). Application of these products in agriculture may contribute to their environmental accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…In a soil-based study, foliar exposure to nano Mn (0.1-1 mg/L) under Fusarium disease stress in soil increased tomato fruit yield by 6.2%, when compared to bulk Mn, which increased fruit yield by 31% and Mn salt, which had no effect. In contrast, eggplant fruit yield was increased 22% by nano Mn, reduced 6.6% by bulk Mn and unaffected by Mn salt when compared to control plants [15]. In other studies, nano Mn (500 mg/L) increased watermelon fruit yield by about 24 and 17.5%, dependent on whether the soil was infested or not with soil-borne disease pathogens.…”
Section: Effect Of Mn Type On the Vegetative And Reproductive Growth mentioning
confidence: 69%
“…However, the literature contains very few studies that are focused on nano-Mn behavior in plant systems, particularly when compared to the number of reports on nano-ZnO, nano-CuO, or nano FeO [9][10][11]14]. The few published studies show that nano Mn treatment resulted in an increase in mung bean growth, 52% and 38%, for root and shoot [3]; a 22% increase in eggplant yield [15]; non-significant effects on root elongation of White Mustard [16]; no effect on lettuce germination, but a dose-dependent increase in plant root length [17]; and, suppression of disease progression over time in watermelon that was not accompanied by significant yield increase [18].…”
Section: Introductionmentioning
confidence: 99%
“…These results are important for future field applications where low amounts of TDNS can be used under controlled conditions on young plants, thereby reducing the risk of human and environmental exposure to nanostructures . The study showed that TDNS can protect faba bean against BBSV by direct effects on the virus or by improving the plant's own defenses through induced resistance, or by both mechanisms together.…”
Section: Discussionmentioning
confidence: 86%